Exploring the influence of brand innovation on marketing performance using signaling framework and resource-based theory (RBT) approach - Grigoriou, N.; Davcik, N.; Sharma, Piyush (Academy of Marketing Science, 2016)
Consumer markets are imperfect and asymmetric information exists between consumers and firms. Firms signal credible production and commitment to consumers by applying different levels of production and market standards. From consumer’s perspective, production standards are a proxy for product quality and a strong signal of the performance that they can expect from the product. The strong market credibility lowers the consumer’s information search cost and thus provides greater overall utility to consumers (Erdem and Swait 2004). Signaling theory suggest that brands are an important medium of quality assessment between the consumers and firms. This theory can be useful for describing behavior when two parties have access to different levels and types of information. One of the ways consumers can resolve their uncertainty is through signals from the brand, yet signaling theory does not address how this mechanism affects brand performance and influences a firm’s success and competitiveness. Resource based theory (RBT) can help bridge this knowledge gap as it incorporates traditional strategy insights concerning a firm’s distinctive capabilities (Mahoney and Pandian 1992).